(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pseudomonas aeruginosa is known to be a major causative pathogen for otitis media (OM), which is still one of the most common infections that affect both adults and children, especially in chronic cases. The prevalence, antimicrobial susceptibility, and biochemical properties of P. aeruginosa isolated from OM patients were examined in this study. 110 (46.81%) of the 235 ear swab samples that were cultured tested positive for microbial growth; the incidence was higher in females (60.43%) than in males (39.57%). P. aeruginosa made up 20% of the isolates and was primarily found in chronic OM (75.74%). Gramme staining showed that 60% of the organisms were Gram-negative, compared to 40% that were Gram-positive. The typical profile of P. aeruginosa was confirmed by biochemical testing: motility, citrate utilization, catalase and oxidase positivity, gram-negative, and negative VP, MR, and urease tests. Complete resistance to amoxicillin was shown by antimicrobial susceptibility, whereas high sensitivity to amoxicillin/clavulanic acid (86.36%), cefepime (63.64%), imipenem (63.64%), and amikacin (59.09%) was noted. The results underline the clinical significance of P. aeruginosa as a persistent pathogen in OM and the need for regular testing for antibiotic susceptibility in order to direct efficient treatment. For patients with P. aeruginosa-associated otitis media, targeted treatment approaches are crucial to lowering the development of resistance and enhancing clinical results.